Kecerdasan Buatan sebagai Simulakra Pendidikan: Analisis Kritis terhadap Krisis Nilai dan Otoritas Keilmuan Pesantren - Fikri, Mohammad; Muslim, Muhammad; Yakin, Fajar Ainol (Journal of Islamic Education and Pedagogy, 2025)
Artificial Intelligence (AI) has transformed the global educational landscape; yet in the pesantren context, it emerges not merely as innovation but as an epistemological force that challenges traditional authority and the sanctity of ‘ilm muktabar. Drawing on a systematic synthesis of 20 recent scholarly articles, this paper investigates the narrative construction surrounding AI adoption in Islamic boarding schools through a counter-epistemology lens. The findings reveal cultural resistance, spiritual tensions, and deep concerns over digital colonialism. Rather than simply enhancing pedagogy, AI provokes theological unease and apprehension over the commodification of knowledge. The term "Educational Dajjal" is invoked as a critical metaphor, portraying AI as a seemingly redemptive force that may, paradoxically, erode the authenticity of Islamic scholarly traditions. The study calls for an ethical and spiritual repositioning in technological integrationone that transcends technical adaptation and embodies the epistemic values of pesantren.